Allometric equations to estimate growth rates of Myroxylon balsamum, Minquartia guianensis and Otoba parvifolia in the Ecuadorian Amazon - López-Tobar, Rolando (2018)
The evaluation of the analysis of the growth rates of the forest species Myroxylon balsamum (L.) Harms (Balsamo) and Minquartia guianensis Aubl. (Guayacan negro) and Otoba parvifolia (Doncel), established in research stands at the Jatun Sacha Science Station (JSSS), at the age of 20, was the main reason for this research. According to the results obtained it was found that the Balsamo needs 59 years to reach the 60 centimeters of Minimum Cutting Diameter (DMC) that is determined by Ministerial Agreement 039 of the Ministry of the Environment, the Guayacán Negro Huambula, needs 69 years to arrive To the 40 centimeters of diameter, whereas the Doncel needs 27 years to obtain 50 cm of diameter.